Professor of mathematics Kazimieras Vytenis Kabaila (1929–1992) 80 years - Jasiūnas, Henrikas; Verikaitė, Vitolda (Lietuvos matematikos rinkinys, 2009)
K.V. Kabaila life review. Bibliographical listing. Advisor of master and doctoral theses.
Keywords: complex variable function theory; differential equations